BIAS GENDER DALAM “KUMPULAN DONGENG” KARYA CHARLES PERRAULT DAN HANS CHRISTIAN ANDERSEN - Dahayu Mirani Arkana Widati; Bambang Yulianto; Muhammad Erwan Saing (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to described the gender bias of character roles, characterization, and story resolution in a collection of fairy tales by Charles Perrault and Hans Christian Anderesen. This research used a qualitative approach by using the narrative analysis method to examine literary works through text. The theory used is Maria Nikolajeva's gender perspective children's literature. The data source of this research is a collection of fairy tales by Charles Perrault and Hans Christian Andersen. The data collection techniques in this research are reading, listening, recording (BSC), and coding techniques. The results found are (1) role gender bias is found in the role of women who are active in the domestic sphere while men are in the public sphere. (2) Gender bias in characterization can be seen from male characters who are strong, tough, and unemotional. On the other hand, female characters are described as fragile and very emotional. (3) Resolution gender bias is found in the happy ending, which is the princess's meeting with the prince's help.